Broadband optical limiting of a novel twisted tetrathiafulvalene incorporated donor–acceptor material and its Ormosil gel glasses. Issue 31 (30th July 2018) - Sun, Jibin; Yuan, Biao; Hou, Xueqing; Yan, Chaoxian; Sun, Xingming; Xie, Zheng; Shao, Xiangfeng; Zhou, Shuyun
Abstract : A novel tetrathiafulvalene incorporated D–A molecule, TTF-Pt(bzimb), was rationally designed and synthesized for broadband optical limiting. Abstract : To accomplish broadband optical limiting with high visible-light region ( ca. 400–700 nm) transmittance, as well as to satisfy the requirement of practical applications, a novel molecule, TTF-Pt(bzimb), has been rationally designed and synthesized by connecting an excellent electron donating tetrathiafulvalene and a Pt(ii )-incorporated electron withdrawing Pt(bzimb) with a C–C triple bond. Chlorine substitutedCl-Pt(bzimb) was presented for comparison. As expected, the theoretical calculation results clearly demonstrate thatTTF-Pt(bzimb) exhibits a twisted conformation with a dihedral angle of 50° at the C–C triple bond. The intramolecular charge transfer existing between the donor and the acceptor is well evidenced by a series of experimental results such as UV-vis spectra, fluorescence spectra, and CV. Benefiting from a unique conformation, TTF-Pt(bzimb) and its doped Ormosil gel glasses in a methyltriethoxysilane matrix exhibit broadband (532 and 1064 nm) optical limiting behaviour with high visible-light transmittance. Furthermore, TTF-Pt(bzimb) shows more remarkable optical limiting behaviour than the state-of-the-art optical limiting material, C60, under 532 nm. Thus, our results disclose a rational molecular design strategy for the accomplishment of remarkable optical limiting.TTF-Pt(bzimb) and its gel glasses can be considered as promising candidates for the applications of optical limiting and for use in nonlinear optical devices.